Students’ Perceptions Of Tiktok As An Alternative Media To Enhance Speaking Skills - Olivia Farisca Adhani; Silih Warni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In language learning, the ability to communicate orally plays a vital role, enabling individuals to interact and understand others in different social situations. Oral communication in language learning is crucial due to its relevance in daily interactions and academic endeavors. The research aims to investigate EFL students' perceptions on using TikTok as a learning tool, particularly its impact on speaking abilities. The study explores the effectiveness of TikTok in enhancing speaking proficiency. Through a descriptive qualitative methodology, the study examines the perspectives of EFL students at a school in Jakarta, Indonesia, regarding the use of TikTok for language learning. Purposive sampling was employed to select participants who utilize TikTok for their English language learning. Data collection involved observation and interviews to gain insights into students' experiences and perceptions. Findings reveal diverse viewpoints among students regarding the utility of TikTok for English language learning, encompassing both positive and negative opinions. While TikTok offers opportunities for exposure to authentic language and engagement with native speakers, challenges such as accuracy and fluency are noted. Despite these challenges, TikTok is recognized as a potential platform for improving speaking skills due to its accessibility and engaging content. This research provides valuable insights into the perceptions of EFL students regarding TikTok's role in language learning. By addressing the research question of students' perceptions of TikTok's effectiveness in English language teaching, the study contributes to understanding the potential of social media platforms like TikTok as supplementary tools for language learning.